GLUT1 deficiency syndrome: a case report with a novel SLC2A1 mutation - Ivančević, Nikola; Cerovac, Nataša; Nikolić, Blažo; Čuturilo, Goran; Marjanović, Ana; Branković, Marija; Novaković, Ivana (Vojnosanitetski pregled, 2021)
Introduction. GLUT1 deficiency syndrome (GLUT1 DS, OMIM 606777) is a metabolic brain disorder caused by mutations in SLC2A1 gene (chromosome 1) encoding glucose transporter type 1 located on blood-brain membrane. The “classic” phenotype in children includes early onset generalized farmacoresistant epilepsy, developmental delay, complex movement disorders and acquired microcephaly. However, there are milder phenotypes without epilepsy which could be seen in older children. The ketogenic diet is a treatment of choice. Case report. We present a four-year- old female patient with farmacoresistant generalized epilepsy, paroxysmal dystonic posturing, ataxia, hypotonia, developmental delay (motor, attention and speech disturbances), and microcephaly. The genetic testing revealed a novel point mutation at c.156T > A (p.Y52X) in exon 3 of SLC2A1 gene. The patient responded excellent on ketogenic diet. Conclusion. GLUT1 DS is treatable, and likely to be under-diagnosed neurological disorder. The ketogenic diet is resulting in good control of seizures in the patients, and it has certain benefit for the neurodevelopmental disability.